Mapping of nighttime light trends and refugee population changes in Ukraine during the Russian–Ukrainian War - Huang, Chaoqing; Hong, Song; Niu, Xiaoxiao; Wu, Qian; Zhong, Yanmei; Yang, Huan; Zhang, Haoran (Frontiers in Environmental Science, 2023)
Nighttime lights provide a true and coherent reflection of human activities. In this study, we used nighttime lights data to analysis spatial-temporal changes of nighttime lights in Ukraine quantificationally before and after the war. We then combine Sen's slope with Hurst index to analysis the trend of nighttime lights in future. Finally we build a linear model using nighttime lights data and part of refugee data from UNHCR through statistical analysis, which can well explain the relationship between the refugee population and the total nighttime lights DN value. Our results showed that one week after the Russia-Ukraine war began, the nighttime lights area, average nighttime lights DN value in Ukraine displayed a rapid downward trend, in which the nighttime lights area decreased by 53.97%, the total nighttime lights DN value decreased by 53.18%, we also mapping a nighttime lights trend in future of Urkraine. Our result estimated by the relationship between refugee population changes and nighttime lights in this study, were basically consistent with the data from UNHCR. Our analysis showed that nighttime light data can be directly used to estimate, dynamically, the spatial-temporal changes of refugees movements during war, which has great significance for international humanitarian assistance and post-war reconstruction.